Capillary water absorption by a porous cylinder. (September 2018) - Hall, Christopher
Capillary absorption (imbibition) of water by a porous cylinder is described by means of a Sharp-Front model. The cumulative absorption increases as (time) 1/2 at early times, but more slowly as the wet front approaches the cylinder axis. Results are given in terms of dimensionless variables. Experimental data on plaster cylinders are in good agreement with theory. Estimates of the sorptivity and effective porosity of the material can be obtained. The model may be useful in testing drilled cores and may also be applied to radial flow through the wall of a porous tube (hence to conduits and arches).